Критерій оптимізації фільтра дробового степеня для цифрової кореляції спекл-зображень - Муравський, Л.І.; Половинко, Т.І.; Голинський, І.С. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The criterion of fractional power filter optimization for digital speckle correlation is proposed. Its analysis is conducted and results of the criterion approval on real speckle images of studied composite material surface are shown.